Online identification of time‐delay jump Markov autoregressive exogenous systems with recursive expectation‐maximization algorithm - Chen, Xin; Zhao, Shunyi; Liu, Fei (International journal of adaptive control and signal processing, 2020)
Summary This article considers the identification problem of the jump Markov autoregressive exogenous (JMARX) systems with unknown invariant time‐delay under the framework of recursive expectation‐maximization (REM) algorithm. In this article, a recursive Q‐function is formulated for the JMARX systems, based on which the recursive sufficient statistics are obtained. Then, the parameter vectors, variance, transition probability matrix, and time‐delay are recursively estimated. A numerical example and a simulated continuous fermentation reactor process are employed to illustrate the effectiveness of the proposed algorithm.